2016
DOI: 10.1088/0953-4075/49/23/234001
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical configuration and selective excitation of the chiral molecule halothane

Abstract: X-ray single-photon ionization and fragmentation of the chiral molecule halothane (CHBrClCF3) from a racemic mixture have been investigated using the COLTRIMS (Cold Target Recoil Ion Momentum Spectroscopy) technique. Two important facets related to the core ionization of this species are examined: Firstly, the distinction of enantiomers (mirror iso-1 arXiv:1609.07913v1 [physics.chem-ph] 26 Sep 2016 mers) and the determination of absolute configuration on a single-molecule level by four-body Coulomb explosion; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…In this case, the probability of chirality-sensitive coincidence events dramatically decreases as the number of fragment pathway increases. Pitzer et al showed that incomplete fragmentation (partial break-ups), corresponding to four-fold and even threefold coincidence events of five-atom (CHBrClF)[244] and eight-atom (CHClBrCF3) molecules[245], can also be used to identify enantiomers. In addition, the same authorsexamined site-selective excitation of chiral C*HClBr−CF3 containing two carbon atoms by varying the photon energy so that only the stereogenic carbon center C* (299.0 eV) or both carbon atoms (305.0 eV) are excited [245].…”
mentioning
confidence: 99%
“…In this case, the probability of chirality-sensitive coincidence events dramatically decreases as the number of fragment pathway increases. Pitzer et al showed that incomplete fragmentation (partial break-ups), corresponding to four-fold and even threefold coincidence events of five-atom (CHBrClF)[244] and eight-atom (CHClBrCF3) molecules[245], can also be used to identify enantiomers. In addition, the same authorsexamined site-selective excitation of chiral C*HClBr−CF3 containing two carbon atoms by varying the photon energy so that only the stereogenic carbon center C* (299.0 eV) or both carbon atoms (305.0 eV) are excited [245].…”
mentioning
confidence: 99%
“…We achieved a recycling efficiency of >95 % per cycle. Experiments with this recycling scheme have successfully been performed using methyloxirane (C3H6O) [33][34][35], bromo-chloro-fluoro-methane [9,10,36,37], halothane [38], trifluoro-methyloxirane (C3H3F3O), and deuterated formic acid (CHOOD) [39], with vapor pressures from 10 to 600 mbar.…”
Section: Discussionmentioning
confidence: 99%
“…A first step was performed recently by recording the Coulomb Explosion of a racemic mixture of halothane (2-bromo-2-chloro-1,1,1-trifluoroethane, CHBrClCF 3 ). [20] One of the fragmentation pathways yielded the fragments CH + , Cl + , Br + and CF 3 + . Although there is some background present, a good separation of enantiomers can be observed.…”
Section: Prospects and Limitations For Larger Moleculesmentioning
confidence: 99%